Perceptions of the users of urine diversion dry (UDD) toilets in medium density mixed housing in Hull street, Kimberley - Matsebe, Gertrude Nomsa (My University, 2012)
South Africa is a water-scarce country (Otieno and Ochieng, 2004; Wassung, 2010). The current sanitation system mostly used in South African urban areas depends on extensive use of water in a form of flush toilets. The housing sector in major cities is continuously growing and this is putting a strain on water services. The government has explored a range of sanitation technologies including waterborne, the Ventilated Improved (VIP) toilet and ecological sanitation (widely known as ecosan) in a form of a urine diversion dry (UDD) toilet. The latter provides a reasonable solution to the current sanitation challenge. This study explores the perceptions of the users of the UDD toilets installed in the medium density mixed housing development of Hull Street in Kimberley. Understanding the users’ socio-cultural perceptions of the UDD toilet will contribute to future policy making, as the information can be used to improve the future roll-out of the technology in order to make it more acceptable. The study was qualitative in nature and used a phenomenological research design. The sample size comprised 16 participants, 13 of whom were residents of the Hull Street housing project and three were employees of the Sol Plaatje Housing Company (SPHC). The sample was selected by a purposive sampling method. Semi-structured interviews were conducted to collect data for the study. The data was analysed by means of content analysis, which enabled the researcher to identify important themes for the study. The findings of the study revealed dissatisfaction regarding the use of the UDD toilet, which emanates from poor design of the toilet facility. The research was successful in identifying, inter alia, odour, uncomfortable sitting position on the toilet mainly by female users and high cost of operating and maintaining the sanitation system. Recommendations emphasise the importance of involving users in future UDD sanitation projects and educating the public at large about sustainability aspects of this sanitation technology (UDD). One of the key lessons drawn from the study is that challenges experienced by the users should be used to improve future UDD toilets.
Keywords: Ecological sanitation; UDD sanitation system; Socio-cultural perceptions